Charge: uma prática discursiva e ideológica - Miani, Rozinaldo Antonio (9 Arte (São Paulo), 2012)
This paper presents a reflection on the charge, understood as a kind of iconographic languages, whether lecture and intertextual, and which is characterized as an ideological and discursive practice. We seek to identify the key policy elements, aesthetic, and language that make up the universe definition of charge, acknowledging its historical and determining its condition ideological sign. We believe that the charge carries a persuasive nature of discursivity, so revealing and advocate ideas, and also na ideological expression, while communicative strategy in various socio-political contexts.